Optical Coherence Tomography Angiography: Principles and Application in Retinal Diseases - Gabriella Moraes; Livia Faes; Bishwanath Pal (Delhi Journal of Ophthalmology)
The non-invasive imaging technology of optical coherence tomography angiography (OCT-A), has been claimed to potentially revolutionize the management of patients suffering from retinal disease. Its use in retinal diseases such as diabetic retinopathy (DR), age related macular degeneration (AMD), and retinal vein occlusion (RVO) has been expanding significantly over the last years. However, as any other imaging technique, limitations and artifacts need to be considered for its correct interpretation. Further studies are needed to assess the diagnostic properties of OCT-A as a patient management tool for retinal diseases. To what extent the potential of OCT-A will translate into daily medical routine still needs to be established.